2009
DOI: 10.1007/s12524-009-0041-7
|View full text |Cite
|
Sign up to set email alerts
|

A neural network based urban growth model of an Indian city

Abstract: The aim of the study reported in this paper is to demonstrate that the subjectivity in urban growth modeling and the calibration time can be reduced by using objective techniques like Artificial neural network (ANN). As a case study, the ANNbased model was applied to simulate the urban growth of Saharanpur city in India. In the proposed model, remote sensing and GIS were used to generate site attributes, while ANN was used to reveal the relationships between urban growth potential and the site attributes. Once… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 26 publications
1
37
0
4
Order By: Relevance
“…Maithani sites and orchard) and achieved an overall accuracy of 83%. Similar work on ANNbased urban growth modelling was also reported by Pijanowski et al (2002aPijanowski et al ( , 2002bPijanowski et al ( , 2005, Thapa and Murayama (2012), Arora et al (2004), Maithani (2009) and Maithani et al (2010).…”
supporting
confidence: 73%
“…Maithani sites and orchard) and achieved an overall accuracy of 83%. Similar work on ANNbased urban growth modelling was also reported by Pijanowski et al (2002aPijanowski et al ( , 2002bPijanowski et al ( , 2005, Thapa and Murayama (2012), Arora et al (2004), Maithani (2009) and Maithani et al (2010).…”
supporting
confidence: 73%
“…Yeh and Li [7] had identified seven spatial variables to represent the site attributes of each cell for the simulation of urban development viz., (i) distance to the major urban areas; (ii) distance to suburban areas; (iii) distance to the nearest road; (iv) distance to the nearest expressway; (v) distance to the nearest railways; (vi) neighbourhood development level; and (vii) agricultural suitability. Maithani [8] had identified that urban growth is defined as a function of the following three factors, also called as causative factors which are (i) accessibility to roads (connectivity is a major factor affecting the urban growth process); (ii) accessibility to the city core, (most of the higher level facilities are located in the city core); and (iii) accessibility to infrastructural facilities. Almeida et al [9] had used an extensive list of twelve variables for determining urban land use change through simulation viz., (i) area served by water supply; (ii) mediumhigh density of occupation (25% to 40%); (iii) existence of social housing, (iv) distances to ranges of commercial concentration; (v) distances to industrial zones; (vi) distances to residential zones; (vii) distances to peripheral residential settlements; (viii) distances to isolated institutional use; (ix) distances to main existent roads; (x) distances to the service and industrial axes; (xi) distances to planned roads; and (xii) distances to peripheral roads.…”
Section: Variables Influencing Urban Growthmentioning
confidence: 99%
“…Substantial amount of studies have adopted these theories to explain the complex system being represented in the model (Batty and Xie, 1994;Li and Yeh, 2002a;Maithani, 2009;White and Engelen, 1993). The incorporation of neural networks, cellular automata and artificial intelligence implicitly implements these theories in urban studies (Manson, 2001).…”
Section: Theories Supporting the Development Of Dynamic Modellingmentioning
confidence: 99%
“…China, between 2008 and 2012, an increasing interest in urban modelling using CA has been observed in other Asian countries, notably Japan, Korea, Malaysia and Nepal (Guan et al, 2011b;Kim, 2009;Maithani, 2009;Naimah et al, 2011;Samat, 2006;Thapa and Murayama, 2011). Applications of CA in USA, Europe, or China reflect more on the leading research clusters rather than the urban growth challenges faced by major cities in the world.…”
Section: Spatial Distribution Of Ca's Studymentioning
confidence: 99%
See 1 more Smart Citation